Shaping police self-efficacy: a content analysis of officer views towards their duty assignments, working locations, and working times - Somers, Logan J. (Journal of crime and justice, 2026)
While it is thought that different work experiences generate unique situations that allow police officers to develop confidence in their abilities to resolve them, this connection has received scarce scholarly attention. In the current study, a thematic content analysis of narrative survey responses from over 300 police officers from one large agency in the United States was conducted to assess perceptions of how and why work contexts might differentially shape self-confidence. Participants believed that officers who are exposed to a variety of workplace experiences develop into the most confident practitioners. Working patrol assignments, in high crime areas, and on night shift were viewed as especially important. Overall, the findings offer useful insights for police agencies looking to build self-confidence within their sworn personnel and numerous avenues for future research to expand on this work.